AI-Powered NLP in Vernacular Public Relations: Opportunities, Challenges, and Ethical Implications for India’s Multilingual Landscape - Unnikrishnan, Sharanya; Thomas, Eldhose; Dey, Arunima (The Scientific Temper, 2025)
India is currently experiencing a rapid growth in digital space and it is estimated that by 2025 more than 850 million people will be given access to the internet. The significant percentage of these users has shown they favor regional languages to English and this trend poses a serious strategic need to the PR practitioners to communicate to audiences in culturally relevant forms especially in the Tier-2 and Tier-3 urban centers and even in rural areas. Natural language processing tools that are powered by Artificial Intelligence are emerging as revolutionary facilitators that have the potential to provide mass localization of content, sentiment monitoring, and crisis management across this linguistic mosaic. However, the problematic issues continue to persist, including the heterogeneity of dialects, the lack of strict data sets, the possibility of bias in the algorithms, and the general ethical dilemma. The research methodology used in this treatise is qualitative and secondary and is through synthesis of scholarly sources, industry reports, and empirically-driven case studies that were published between 2017 and 2023. Four main areas have been revealed through the thematic analysis, in which AI-NLP reconfigures the public relations praxis: localization of content, media monitoring and sentiment analysis, cultural adaptation, and ethical deployment. Case studies based on various industries, such as e-commerce (Amazon India), governmental efforts (COVID-19 outreach), and politics (2024 Lok Sabha campaigns) demonstrate measurable changes in the indicators of engagement, trust levels, and inclusiveness of the audience. The results point out that AI-driven vernacular PR is associated with an increased trust of the audience, reduction of communicative disparities, and the ability to implement cost-efficient and scalable outreach initiatives. However, their effective application requires hybrid AI-human processes, culturally sensitive models, and effective regulatory controls, and especially the compliance with the Digital Personal Data Protection Act 2023 in India. This paper, therefore, assumes that vernacular AI is not only a technological creation, but a business necessity that is critical to support multilingual societies that embrace inclusive communication and provide contextualised information that can be applicable to other language-diverse markets.